Increasing Students' Far Jump Ability Using Media - Rahmad Putra Perdana; Edi Purnomo; Eka Supriatna; Ahmad Atiq; Nikolaus Adi Saputra; Ahmad Ropiq Ramadhan; Aditya Aditya (UNIVERSITAS NEGERI MAKASSAR, 2022)
This study aims to determine the increase in the long jump ability of students using media. This research uses the CAR approach (Classroom Action Research). This research was conducted to find information about the implementation of learning variations delivered by classroom action research. Following this type of research, namely classroom action research, this research has staged in the form of cycles. The design of each cycle consists of four stages, namely planning, implementation, observation, and reflection. From the results of the study, it was found that in the learning outcomes in cycle 1 9 students had not achieved the completeness score because they got scores below 75 and 13 other students were declared complete after getting a score above 75, as for the completeness score in the lessons at school. is 75. In the pre-cycle, the average value of student learning outcomes is 75%. Then from the learning outcomes in cycle 2, 2 students had not achieved the completeness score because they got a score below 75 and 35 other students were declared complete after getting a score above 75, while the completeness score in the lessons at school was 75. So it can be concluded that there is an increase in the long jump ability of students using media with the evidence that students are not completely reduced.